Increasing Company Value: The Role of Profitability and Capital Structureand Tax Avoidance as Mediation - Diana Sari; Yati Mulyati; Dyah Purnamasari (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
Firm value is an important factor in the view of investors as well as a form of success for managers in managing the company. In addition to success for managers, company value can also have an impact on increasing stock prices. The purpose of this study is to see how the influence of capital structure, profitability and tax avoidance on firm value. The samples selected in this study were 59 technology sector companies listed on the Stock Exchange and the Singapore Stock Exchange for the period 2017 to 2022. The sampling technique used in this study was to use side non-probability using a purposive sampling method. Data analysis in this study uses path analysis with the help of Smart-PLS software to test the proposed model. The results of this study indicate that the three variables consisting of capital structure, profitability and tax avoidance have a significant positive effect on firm value. Likewise, the role of tax avoidance was found to be a variable that mediates between capital structure and profitability on firm value.